Acoustic surveying for beaked whales in the Coral Sea as a mitigation measure for naval exercises - Cato, D.; Savage, M.; Dunlop, R.; Parnum, I.; Blewitt, M.; Sue, G.; Donnelly, D.; Cleary, J.; McCauley, Robert (2010)
Beaked whales have been over-represented in whale strandings that have occurred at similar times and places of some naval exercises in the northern hemisphere. Although whale strandings are common, it is unusual to find beaked whales stranded in such large numbers. Consequently, the environmental management of naval exercises requires mitigation measures to avoid potential impact on beaked whales. This requires some knowledge of beaked whale distributions and behavior, but little is known about beaked whales, less than for all other whales. Beaked whales are small whales that inhabit deep water. They are particularly elusive and rarely seen at sea. Much of what little is known about them results from the few that have been washed ashore. Visual surveying has proved to be generally ineffective. Beaked whale vocalizations are, however, sufficiently distinctive to allow passive acoustic detection and classification [1]. The sounds are sufficiently distinctive to distinguish them from those of other toothed whales, though these distinctions are subtle. All toothed whales produce echolocation clicks or pulses with a small number of cycles and most energy at ultrasonic frequencies. Beaked whale clicks can be distinguished by the frequency range, duration and number of cycles but other species have clicks that are close in one or other of the characteristics. In 2008 and 2009 we conducted two passive acoustic surveys of a naval exercise area in deep water in the Coral Sea (north east of Fraser Is.) in an attempt to determine the distributions of beaked whales in the area of about 18, 900 square km. Each survey was three weeks duration and involved acoustic and visual observations. A towed array of two hydrophones with frequency response to 150 kHz, and two drifting systems with hydrophones at 400 m depth and response to 96 kHz were used (beaked whale sounds have an upper limit of about 80 kHz). The drifting systems were tracked using a radio link suspended from a buoy that transmitted the GPS position of the buoy at regular intervals. Nothing was known about the presence of beaked whales in the area, but there are records of stranding of four species on the nearest part of the Queensland coast. Two of these species were the same as those recorded with the DTAGs. Almost 400 h of recordings were obtained using the towed array and almost 200 h from the drifting systems. Thousands of toothed whale clicks were recorded. Some of the clicks recorded were remarkably similar to those published for beaked whales [1, 2] and so were identified as beaked whales. Only a small proportion of clicks were typical of beaked whale sounds and these were recorded mainly over the steep slopes of two coral islands. The analysis is continuing © 2010 CROWN.